Four new species of Entoloma (Entolomataceae, Agaricomycetes) subgenera Cyanula and Claudopus from Vietnam and their phylogenetic position - Morozova, Olga; Popov, Eugene; Alexandrova, Alina; Pham, Thi Ha Giang; Noordeloos, Machiel Evert (Phytotaxa, 2022)
Three new species of Entoloma subgenus Cyanula (Entoloma argus, E. arion, and E. icarus) from Kon Chu Rang Nature Reserve and one species of subgenus Claudopus (E. daphnis) from Cat Tien National Park were discovered during an investigation of the diversity of the mycobiota of Central and South Vietnam and are described here. Illustrated descriptions of their macro- and microscopic features and discussion of similar taxa are given. Phylogenetic analysis was based on nrITS1-5.8S-ITS2 and nrLSU regions. The results confirm the polyphyletic origin of the pleurotoid basidiocarp form in the genus Entoloma.